Density Visualization Pipeline: A Tool for Cellular and Network Density Visualization and Analysis - Grein, Stephan; Qi, Guanxiao; Queisser, Gillian (Frontiers in Computational Neuroscience, 2020)
One of the most heterogeneous type of cortical neurons are GABAergic interneurons. Despite this fact they are represented by a rather small fraction of the neuronal population in the neocortex. Nonetheless these interneurons balance excitation and inhibition in a highly dynamical network and are important for a large variety of cortical function. Thus classification of the GABAergic interneurons is of crucial importance to understand on the one hand their various functions and on the other hand their ubiquitous appearance in the neocortex. In this paper we developed a density visualization pipeline (DVP) which computes, visualizes and quantifies the density distribution, the `mass' of interneurons. The DVP reads common neuromorphological file formats, e.g. Neurolucida XML files, NeuroMorpho.org SWC files and plain ASCII files. Full 3d visualization and projections of the density to 1d and 2d manifolds are supported by the DVP. All routines are embedded within the visual programming IDE VRL-Studio for Java which allows the definition and rapid modification of analysis workflows. All methods were tested on morphological data of interneurons and pyramidal neurons in the barrel cortex.